Sublingual immunotherapy increases Treg/Th17 ratio in allergic rhinitis - Wang Jiarong (De Gruyter, 2021)
Few studies investigated the effects of sublingual immunotherapy (SLIT) on the peripheral regulatory T cells (Tregs)/Th17 ratio.